Utilization of Medical Waste Ash as Planting Media: A Preliminary Review - Kiki Umizakiah; Gemilang Lara Utama Saripudin; Martha Fani Cahyandito (Jurnal Ilmu Lingkungan, 2025)
The expansion of healthcare services has significantly increased medical waste generation, with incineration serving as the primary method for volume reduction and pathogen inactivation. This process produces medical waste ash (MWA), classified as hazardous due to its strong alkalinity and the presence of potentially toxic metals (PTMs). Although the physicochemical characteristics of MWA have been widely reported, a critical synthesis of its potential utilization as planting media, particularly in integration with organic amendments, remains limited. This narrative review analyzes multidisciplinary literature published between 2000 and 2025 to assess the technical feasibility and environmental implications of such utilization. Across diverse geographical contexts and incineration technologies, MWA consistently exhibits high alkalinity (pH >10) and is predominantly composed of CaO (10–62 wt.%) and SiO₂ (1–58 wt.%). The presence of nutrient-related oxides, including K₂O, MgO, SO₃, and P₂O₅, indicates potential agronomic functionality, particularly for non-food cultivation systems. However, PTMs such as Zn, Pb, Cr, Cu, Ni, Cd, and Hg are consistently detected, with mobility influenced by combustion conditions, waste composition, and ash fractionation. Literature synthesis suggests that blending MWA with organic amendments may stabilize pH, enhance nutrient availability, and facilitate PTM immobilization through chelation mechanisms. From a circular economic perspective, MWA valorization may reduce disposal volumes, transportation demand, and long-term environmental burdens associated with landfilling. Nevertheless, the existing body of research remains largely laboratory based. Rigorous experimental validation, standardized toxicity assessment, and large-scale field trials are therefore required to ensure agronomic performance and long-term environmental safety before broad implementation.